Pengaruh Ukuran Perusahaan, Profitabilitas, Leverage dan Kepemilikan Institusional Terhadap Ketepatan Waktu Penyampaian Laporan Keuangan (International Forum of Researchers and Lecturers, 2023)
This study aims to examine the effect of firm size, profitability, leverage and institutional ownership on the timely submission of financial reports. This research uses secondary data from property and real estate companies listed on the Indonesia Stock Exchange in 2019-2022. The samples obtained in this study were 13 companies during the 2019-2022 period with a total sample of 52 annual financial reports selected through purposive sampling. The data analysis method used in this study is logistic regression using SPSS. The results of the study show that company size, profitability and institutional ownership have no effect on the timeliness of submission of financial statements. While Leverage has a positive effect on the Timeliness of Submission of Financial Statements.